Interregional cooperation in the development of region industry in the context of economic sanctions - R. F. Gataullin; E. R. Chuvashaeva (Вестник университета)
Increasing the competitiveness of industrial production largely depends on the development of interregional cooperation, which implies a deepening of specialization. The other side of cooperation is the expansion of interregional exchange. In modern conditions, cooperation and exchange ties extend not only to the domestic market, but also to the external one. Dependence on foreign markets has already become decisive for many countries today. Different regions of Russia depend on foreign markets in different ways. These differences also apply to activities. The article discusses the content and tasks of restructuring ties for cooperation in the industry of the Republic of Bashkortostan in the context of economic sanctions. Among the emerging problems are the narrowing of sales markets, breaks in technological chains and the associated decrease in the level of innovation and competitiveness of enterprises. The mechanism for restoring the integrity of production chains is shown, including the reorientation of the exchange to friendly countries, the search for and finding sources of goods and services within the country, for which it is proposed to organize joint production of components and expand their existing production facilities, with the involvement of potential consumers.